Risk, Unemployment, and the Stock Market: A Rare-Event-Based Explanation of Labor Market Volatility - Kilic, Mete; Wachter, Jessica A (Review of Financial Studies, 2018)
What is the driving force behind the cyclical behavior of unemployment and vacancies? What is the relation between firms’ job-creation incentives and stock market valuations? We answer these questions in a model with time-varying risk, modeled as a small and variable probability of an economic disaster. A high probability implies greater risk and lower future growth, lowering the incentives of firms to invest in hiring. During periods of high risk, stock market valuations are low and unemployment rises. The model thus explains volatility in equity and labor markets, and the relation between the two. Received May 12, 2016; editorial decision October 26, 2017 by Editor Stijn Van Nieuwerburgh. Authors have furnished data, which are available on the Oxford University Press Web site next to the link to the final published paper online.